THE CALCULATION OF WOODEN CONSTRUCTIONS TAKING INTO ACCOUNT THE CREEP OF WOOD ON THE EXAMPLE OF A STATICALLY INDETERMINATE LENTICULAR BLOCKED TRUSS - I. S. Inzhutov; V. V. Mezentsev; A. F. Rozhkov; M. E. Khovansky (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives The aim of the study is to refine the calculation of wooden constructions, in particular, to use variable elastic modulus  for the calculation of the second group of the limiting state in order to predict the deformations more accurately.Methods The study is carried out using the method of creep  consideration based on the use of either variable elastic modulus or  the “modulus of total deformations” for the calculations. These  moduli, besides the elastic, account for residual deformations, while  the fraction of the latter increases with increasing stress levels in the wooden elements.Results The calculation of statically indeterminate spatial timber-metallic lenticular block-truss loaded with a uniformly distributed  load is carried out. At the first stage, the construction was calculated using the elastic modulus of all wooden elements E =  10000 MPa in accordance with the set of rules (SP 64.13330.2011  (updated version of SNiP II-25-80). At the second stage, the elastic  modulus was replaced by variable, i.e., matched to the level of  stresses in the elements by means of interpolation. The obtained  deflection values are analysed and compared to the construction  limiting value. The study was conducted without taking into account the flexibility of node connections and defects of the wood, which  can also have a significant effect on the deflection value.Conclusion The use of a variable elastic modulus for calculations  significantly influences the magnitude of deformations (in our case,  deflections are increased by 30%). The study confirms the need to  take into account the creep of wood and refine the calculations of  wooden structures. Such approximating dependence at different moisture levels of wood will allow the calculation of wooden  structures to be performed at a higher theoretical level.